Participation and mediation: key elements to forewarn and resolve conflicts during droughts [Part 1. Components of drought planning. 1.2. Organizational component] - Celaya N.; Rodríguez Perea A.; Carbonell X. (Drought management guidelines technical annex, 2007)
Droughts can result in restrictions to water supplies, which cause alarm in towns and cities or wherever they are enforced, a situation the news media never fails to cover with photos of deserts and death disseminated far and wide. It is clear droughts place hydraulic systems under an extreme amount of strain -especially rivers and aquifers. It is therefore essential to make use of successful experiences to create a new conception of the field. It will however take some time for this to be accepted as the norm, since drought management will continue to generate situations involving conflict between the interests and values of different individuals and groups.